Nieizotermiczny Przepływ Gazu w Gazociągach Dalekosiężnych - Walden, H. (Engineering Transactions, 1961)
The above problem of gas flow is considered in the range of quadratic in engineering computations, isothermal gas flow is assumed for long range gas lines. This as assumption may impair in some cases the accuracy of the equations. It has been found experimentally that under certain conditions there is a temperature variability along the entire gas line. In other cases the temperature curve is composed of isothermal and non-isothermal segments. A generalized equation is derived for the computation of non-isothermal flow in long range gas lines. For T = const we obtain, as a special case, the known relation for the isothermal flow.